Challenges of Artificial Intelligence in developing the scientific research system (Bibliouniversitas@ABRM.md, 2025)
This article explores initiatives that promote responsible evaluation of researchers and scientific practices, mutual reinforcement, and support for research evaluation reforms. It discusses the role of Artificial Intelligence in scientific research, which is transforming the academic environment, specifically through data analysis and modern assessment methods. The article highlights organizations that address these challenges, including GraspOS, Science Europe, and Clarivate. The study also presents Webometrics rankings and the value of scientific contributions in Google Scholar, ORCID, and the "AD Scientific Index." Additionally, it provides an evaluation
Keywords: artificial intelligence; scientific research; Google Scholar